Punk Community Activism: Seizing Urban Space (A Comparison between Indonesian and Malaysian Punk Communities) - Sokowati, Muria Endah; Annuar, Sharifah Nursyahidah Syed (Universitas Semarang, 2025)
Purpose: We compared two punk communities: Lamidet Society (Yogyakarta) and Rumah Api (Kuala Lumpur) in conducting the activism movement related to urban issues; and identified the strategy used to fight the authorities, analysed how both communities adapt the spirit of resistance of the punk culture to the local culture and politics. Methods: This study used in-depth interviews and participant observation to obtain deeper insights into the experiences and comparisons of punk community engagement in Yogyakarta and Kuala Lumpur. It also conducted a content analysis of interviews, encompassing zines, internet platforms, and lyrics to elucidate their ideology and socio-political statements regarding the appropriation of urban places. Findings: Lamidet Society and Rumah Api diverge in their particular emphases, modes of expression, scale of scenes, and cultural contexts, reflecting the unique social and political landscapes in each country and the diverse nature of punk activism within the broader punk subculture. Thus, the dynamic character of these movements remained shaped by their specific circumstances and local conflicts in Indonesia and Malaysia. Originality: This study addressed the demand for innovation by examining punk culture, particularly its evolution into a global phenomenon and its capacity to highlight local issues in the context of resistance against authorities, including urban issues. The juxtaposition of two punk communities in relation to their social and political contexts revealed its inherent novelty. Extensive research has been conducted on punk communities; however, comparative studies between the punk communities in Indonesia and Malaysia remain scarce.